The Impact of the Semantic Transformation of the Concept of Gender on Women’s Policies (Third Sector Social Economic Review, 2026)
This study examines the reflections of the ontological transformation of the concept of “gender” in the social sciences literature on women’s policies within the framework of public policy analysis. It also seeks to answer, through the case of Türkiye, the question of whether abandoning the use of the concept of “gender” in public policy documents corresponds to a policy change or to policy continuity. The study attempts to explain the conceptual transformation and the policy problem through contextual discourse analysis conducted on the basis of the discursive institutionalism approach. Accordingly, while the concept of gender was initially used within a structure of meaning shaped around a focus on “women,” from the 1990s onward the meaning framework of the concept began to transform under the influence of postmodernism and queer approaches. In this process, the concept of gender was reconfigured within a new ontological ground that includes LGBTQ and defines gender along the axis of multiple and fluid “gender identities.” The study finds that this transformation did not remain only at the theoretical level, but also became institutionalized through academic literature and international legal texts. The findings demonstrate that the removal of the concept of “gender” from policy documents in some countries, contrary to interpretations focusing on the terminological use of the concept, does not indicate a regression or discontinuity in the field of women’s rights; rather, it may be regarded as a deliberate strategy of continuity aimed at sustaining women’s policies with a focus on “women.” In this context, the case of Türkiye reveals that the removal of the concept from policy documents does not represent a policy rupture; rather, it may be considered a strategy that enables the continuation of women’s policies with a focus on “women.” Consequently, the study demonstrates the necessity of considering not only the terminological use of concepts in policy analysis, but also the ontological and epistemic foundations on which they are based; and shows that this approach is decisive in terms of preserving the continuity of women-centered policies and ensuring analytical consistency.
Keywords: Gender; ontological transformation; public policy analysis; women’s policies; discursive institutionalism